Diplomasi Pertahanan Dalam Perspektif Hukum Internasional: Strategi Mewujudkan Keamanan Global - Sudarmanto, Sudarmanto (Adagium: Jurnal Ilmiah Hukum, 2025)
Defense diplomacy is a strategic instrument in international relations that emphasizes the use of military power as a means to build trust, prevent conflict, and strengthen security cooperation among states. From the perspective of international law, this form of diplomacy plays a crucial role in the development of norms and international regimes aimed at supporting global stability and peace. This article analyzes the strategic role of defense diplomacy within the framework of international law, employing a normative juridical approach and a qualitative method based on recent literature studies. The findings indicate that defense diplomacy is effective in reinforcing collective security regimes and international norms, although it continues to face challenges related to differing national interests, legal interpretations, and issues of state sovereignty. Strengthening the international legal framework is therefore necessary to ensure that defense diplomacy can be conducted fairly, transparently, and in accordance with the principles of international law.